With or without you: how the G20 could advance global action towards climate-friendly sustainable development - Steffen Bauer; Axel Berger; Gabriela Iacobuta (Deutsches Institut für Entwicklungspolitik (DIE), 2019)
With a collective responsibility for 80% of global greenhouse gas emissions, while representing 80% of global wealth, it is imperative that the countries of the G20 throw their weight behind the implementation of both the Paris Climate Agree-ment and the 2030 Agenda for Sustainable Develop¬ment. In the past, the G20 has demonstrated that it can do that. The G20 Summit in November 2015 in Antalya, Turkey, provided strong support for the climate agreement signed a month later at the UN Climate Change Conference (COP21) in Paris. In 2016 in Hangzhou, China, the G20 adopted an Action Plan on the 2030 Agenda for Sustainable Develop¬ment and committed to “further align its work” with the 2030 Agenda. Even though both agendas have emerged in the multilateral context of the United Nations system, the G20 is expected to exert strong political leadership to address global climate change and to achieve sustainable development. Yet, since 2017 the G20 has struggled to provide such leadership, as support for multilateral commitments, especially those involving ambitious climate actions, appears to be fading. Crucially, opposition to strong multilateral climate policy in the US and Brazil resorts to outright climate denialism at the highest levels of government. These developments are challenging the G20, and BRICS and the G7 for that matter, to sustain support for multilateral commitments on climate and sustainable development. The rise of populist and unilaterally minded parties in European club members may further the risk of side-lining climate and sustainability-related issues in the G20 process. This does not bode well at a time when the G20's support could be a vital ingredient for the success of the United Nations' summits on climate action and sustainable development, both scheduled to convene in New York in September 2019 – less than three months after the Osaka G20 Summit in Japan. Following our analysis, we identify four ways forward that should be conducive to harnessing the G20's economic weight and political clout to push more ambitious global action towards climate-friendly sustainable development, in spite of apparent discrepancies between domestic agendas and global understandings: Strive for strong political declarations in support of the multilateral commitments on climate and sustainable development. Yet, focus at the same time on advancing specific issue-centred initiatives that are palatable to domestic audiences and compatible with the objectives of the Paris Agreement and 2030 Agenda, without framing them as “climate policy” or “sustainability policy”. Embrace non-state and subnational actors as strategic partners to safeguard continuity in times of antagonistic member governments and volatile policies, as well as to build capacities and strengthen implementation of pertinent policies. The so-called G20 Engagement Groups representing business, labour, civil society, women and think tanks are key partners in this respect. G20 workstreams should strive to co-produce specific climate- and sustainability-related initiatives across G20 workstreams as a means to overcome policy silos and to increase ownership and uptake beyond the “usual suspects”. The Think20 (T20) should concentrate – rather than further expand – pertinent expertise and policy advice to leverage crosscutting action by G20 workstreams. Furthermore, detaching its working approach from the official G20 calendar could improve its ability to inform strategic agenda setting.
Keywords: 330; Agenda 2030; Klimawandel